2019
DOI: 10.3390/jcm8101568
|View full text |Cite
|
Sign up to set email alerts
|

Increased Citrullinated Histone H3 Levels in the Early Post-Resuscitative Period Are Associated with Poor Neurologic Function in Cardiac Arrest Survivors—A Prospective Observational Study

Abstract: The exact contribution of neutrophils to post-resuscitative brain damage is unknown. We aimed to investigate whether neutrophil extracellular trap (NET) formation in the early phase after return of spontaneous circulation (ROSC) may be associated with poor 30 day neurologic function in cardiac arrest survivors. This study prospectively included adult (≥18 years) out-of-hospital cardiac arrest (OHCA) survivors with cardiac origin, who were subjected to targeted temperature management. Plasma levels of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…This may point towards different mechanisms for developing ischemic outcomes in cancer and atherosclerosis, respectively [26]. Finally, a recent publication by Mauracher et al demonstrated the predictive value of increased H3Cit for poor 30-day neurologic function in cardiac arrest survivors [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may point towards different mechanisms for developing ischemic outcomes in cancer and atherosclerosis, respectively [26]. Finally, a recent publication by Mauracher et al demonstrated the predictive value of increased H3Cit for poor 30-day neurologic function in cardiac arrest survivors [39].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the implementation of H3Cit measurements in clinical routine is the lack of standardization. However, we used an ELISA for the measurement of H3Cit that has been applied in several other clinical studies [22,24,26,39]. A limitation of our study is its relatively small sample size for both patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…These intervals were established by immediate, structured interviews with the dispatch center, involved emergency physicians, paramedics, or bystander who performed the emergency call. All patients have undergone targeted temperature management with target temperatures between 32 and 34 • C for 24 h. Rewarming was performed at a rate of 0.25-0.5 • C. Resuscitation related parameters were analyzed and reported according to the Utstein recommendations [23,24]. Patient demographics, co-medication, and concomitant diseases were obtained by chart review.…”
Section: Methodsmentioning
confidence: 99%
“…All patients have undergone targeted temperature management with target temperatures between 32 and 34 °C for 24 h. Rewarming was performed at a rate of 0.25–0.5 °C. Resuscitation related parameters were analyzed and reported according to the Utstein recommendations [ 23 , 24 ]. Patient demographics, co-medication, and concomitant diseases were obtained by chart review.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, several accumulating factors might determine patient outcome in CA represented by the balance of dsDNA and DNase: (1) extensive tissue damage, (2) inflammatory signaling, or (3) a reduced capacity to organize and contain the damage response. In this study, we sought to examine the dsDNA/DNase ratio as a predictor of outcome, subsuming a potentially unbalanced degree of cell death and immunological responses in a cohort comparable to previous studies, yet also including a later time point (96 h after CA) to account for a possibly even longer lasting inflammatory reaction [ 12 , 13 ]. Furthermore, we tried to contribute to a better understanding of the ongoing processes in PCAS by investigating novel inflammatory biomarkers (IL-8, MCP-1) on top.…”
Section: Introductionmentioning
confidence: 99%